2017
DOI: 10.18178/ijssh.2017.v7.813
|View full text |Cite
|
Sign up to set email alerts
|

Work-Life Balance and Job Satisfaction: An Empirical study Focusing on Higher Education Teachers in Oman

Abstract: Abstract-With increasing levels of stress, competition and insecurities in life, work-life balance issues have become extremely important. Employees are looking for ways that will help them balance between work and personal life effectively. Researchers have also identified that work-life balance leads to positive organizational outcomes.Although work-life balance has been a frequent subject of inquiry in the Western world, there have been no studies on work-life balance in the Sultanate of Oman. Human resourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(79 citation statements)
references
References 49 publications
6
47
1
4
Order By: Relevance
“…Another studies identified the relationship of employee engagement using SEM (Hanaysha, 2016;Anitha, 2014). Some other previous researchers have also noted to use SEM model aided by Lisrel program (Agha et al, 2017;Sadeli, 2015;Rani et al, 2011;Carmeli et al, 2010). Table 1 demonstrates the validity and reliability of leadership style components.…”
Section: Introductionmentioning
confidence: 99%
“…Another studies identified the relationship of employee engagement using SEM (Hanaysha, 2016;Anitha, 2014). Some other previous researchers have also noted to use SEM model aided by Lisrel program (Agha et al, 2017;Sadeli, 2015;Rani et al, 2011;Carmeli et al, 2010). Table 1 demonstrates the validity and reliability of leadership style components.…”
Section: Introductionmentioning
confidence: 99%
“…An exploration report done by SHRM's (2012) demonstrates that a large portion of the workers respect the connection they have with their immediate supervisor and senior managers as an essential component in their work satisfaction. Work-life balance is tied in with finding the correct harmony amongst work and life, and about feeling good with both work and family responsibilities (Agha et al, 2017). Work-life adjust is the harmony between three segments, in particular, paid work, individual time and unpaid work.…”
Section: B) Extrinsic Motivationsmentioning
confidence: 99%
“…According to Sakthivel and Selvarani (2011), work-life balance plays a vital role in shaping the attitudeof employees towardthe organization, particularly for highly skilled workers like pharmaceutical personnel, where the nature of job is typified with high stress, insecurities in the healthcare work environment, competition and whose commitment present a challenge to employers. According to Agha, Azmi and Irfan (2017) with the increasing levels of stress, competition and insecurities in the healthcare work environment, work-life balance concerns have become tremendously important.In view of this, employees in the healthcare sector are looking for ways that will assist them strike a balance between work and their personal life.For today's healthcare sector, how to heighten organizational commitment and boosttop employee retention is a foremost task (Hsiao-Ping, Chi-Ming, Meei-Ying & Han-Shen, 2019;and Majumder, Giri&Gangopadhyay, 2019).…”
Section: Introductionmentioning
confidence: 99%